Judges and their audiences : a perspective on judicial behavior - Baum, Lawrence (Princeton University Press, 2008)
What motivates judges as decision makers? Political scientist Lawrence Baum offers a new perspective on this crucial question, a perspective based on judges' interest in the approval of audiences important to them. The conventional scholarly wisdom holds that judges on higher courts seek only to make good law, good policy, or both. In these theories, judges are influenced by other people only in limited ways, in consequence of their legal and policy goals. In contrast, Baum argues that the influence of judges' audiences is pervasive. This influence derives from judges' interest in popularity an.